URINARY CATHETER IN URINARY TRACT INFECTIONS WITH THE INFECTION CONTROL RISK ASSESSMENT METHOD ON ASPECTS OF ACTION IN THE HOSPITAL - Kusbaryanto Kusbaryanto; Alika Anisa Nishihara (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2022)
Background: Catheter-associated Urinary Tract Infection (CAUTI) accounts for nearly 40% of all nosocomial infections. This reflects the poor quality of health services. This study aims to analyze the use of urinary catheters for CAUTI with the Infection Control Risk Assessment (ICRA) method in Indonesian hospitals Method: The design of this research is descriptive and quantitative. The population in the study were all nurses who worked in the hospital. The sample used in this study to determine the aspects of action on nurses related to urinary catheter placement were all nurses who worked in the Internal Medicine, Surgery, Geriatrics, and Emergency Units at Panembahan Senopati Hospital Bantul, totaling 61 respondents. The sampling technique used is random sampling. Inclusion criteria are nurse working period 1 year, minimum education D3. The exclusion criteria were respondents who did not fill out the questionnaire completely. Informants in this study were IPCN, IPCLN, internal medicine specialists, emergency room nurse coordinators, and nurses in the inpatient ward.Results: Results: The majority of the procedures from all stages were according to the SOP, at the pre-interaction stage of placing a urinary catheter in male patients, the majority did not wash their hands with running water. At the working stage of installing a male patient's urinary catheter and the installation stage of a female patient's urinary catheter between actions that are in accordance with the SOP and those that are not in accordance with the balanced SOP. Conclusion: The majority of actions from all stages according to SOP and at the pre-interaction stage, a male urinary catheter was inserted, and the majority did not wash their hands with running water.